Feasibility and Challenges for Sequential Treatments in ALK-Rearranged Non-Small-Cell Lung Cancer - Elsayed, Mei; Bozorgmehr, Farastuk; Kazdal, Daniel; Volckmar, Anna-Lena; Sültmann, Holger; Fischer, Jürgen R.; Kriegsmann, Mark; Stenzinger, Albrecht; Thomas, Michael; Christopoulos, Petros (Frontiers in Oncology, 2021)
Background: Anaplastic lymphoma kinase-rearranged non-small-cell lung cancer (ALK+ NSCLC) is a model disease for use of targeted therapies (TKI), which are administered sequentially to maximize patient survival. Methods: We retrospectively analyzed the flow of 145 consecutive TKI-treated ALK+ NSCLC patients across therapy lines. Suitable patients that could not receive an available next-line therapy ("attrition") were determined separately for various treatments, based on the approval status of the respective targeted drugs when each treatment failure occurred in each patient. Results: At the time of analysis, 70/144 (49%) evaluable patients were still alive. Attrition rates related to targeted treatments were approximately 25-30% and similar for administration of a second-generation (2G) ALK inhibitor (22%, 17/79) or any subsequent systemic therapy (27%, 27/96) after crizotinib, and for the administration of lorlatinib (27%, 6/22) or any subsequent systemic therapy (25%, 15/61) after any 2G TKI. The rate of chemotherapy implementation was 67% (62/93). Both administration of additional TKI (median overall survival [mOS] 59 vs. 41 months for multiple vs. one TKI lines, logrank p=0.002), and chemotherapy (mOS 41 vs. 16 months, logrank p<0.001) were significantly associated with longer survival. Main reason for patients foregoing any subsequent systemic treatment was rapid clinical deterioration (n=40/43 or 93%) caused by tumor progression. In 2/3 of cases (29/43), death occurred under the first failing therapy, while in 11/43 the treatment was switched, but the patient did not respond, deteriorated further, and died within 8 weeks. Conclusions: Despite absence of regulatory obstacles and no requirement for specific acquired mutations, 25-30% of ALK+ NSCLC patients forego subsequent systemic therapy due to rapid clinical deterioration, in several cases (approximately 1/3) associated with an ineffective first next-line choice. These results underline the need for closer patient monitoring and broader profiling in order to support earlier and better directed use of available therapies.